Influence of chromophore spacing on the stability and efficiency of host-free sky-blue dendrimer organic light emitting diodes. Issue 21 (16th May 2022) - Graf von Reventlow, Lorenz; Koodalingam, Manikandan; Siebert, Christian; Marlow, Philipp; Puttock, Emma V.; Burn, Paul L.; Colsmann, Alexander
Abstract : Doubly dendronized blue phosphorescent emitters promote more efficient and stable OLEDs than their singly dendronized counterparts. Degradation occurs as red electromer emission attributable to the detachment of the ligands and/or dendrons. Abstract : Combining light emission and charge carrier transport into one molecule simplifies the manufacturing of organic light-emitting diodes (OLEDs). In this work, phosphorescent iridium(iii ) complex-emitters are protected by conjugated dendrons to reduce intermolecular interchromophore interactions that lead to concentration quenching of the luminescence in host-free emission layers. When two dendrons are added to each ligand (doubly dendronized) of an iridium(iii ) complex at the core of the dendrimers ( versus one), the core is found to have improved protection, leading to an enhancement of the external quantum efficiency of the OLEDs from 4% to more than 10%. Likewise, OLEDs comprising the doubly dendronized emitters exhibit improved device lifetimes. A detailed study of the degradation mechanisms reveals that exciton-induced ligand and/or dendron detachment promotes interchromophore interactions (aggregation) that lead to quenching sites and hence red electromer emission inside the OLED emissive layer, with the effects being less pronounced for the doubly dendronized emitter.